Profiling the Contemporary Brazilian Tourism Entrepreneur: A Gender Analysis - Carlos, Costa (2021)
Drawing on the contemporary shift in tourism research to a sociological focus on the producers within tourism, this study profiles Brazilian tourism entrepreneurs through a gender lens. Empirical evidence collected via online questionnaires administered to tourism managers on a nation-wide scale, provides the data on entrepreneurial characteristics such as age, income and educational level. Quantitative analysis utilizing SPSS to correlate variables and test statistical significance is combined with a thorough interweaving of literature on tourism entrepreneurship and gender. This results in a uniquely insightful account of how tourism entrepreneurs’ profiles are influenced by gendered socio-economic structures. Findings, ranging from the high number of male entrepreneurs that earn more than 13 minimum wages, the low number of female entrepreneurs aged 35-39, to the occupational segregation as manifested in a male-dominated transport industry, illustrate how gender silently operates to define entrepreneurial positions. New conceptualizations of entrepreneurship evolve to incorporate the conflicting pressures between the need to conform to entrenched gender roles and simultaneously provide economically in the increasingly unstable and demanding economic landscape. These alterations prompt for the development of tourism policies that recognize and address these gendered influences within tourism development.